PERAN DAUN TEMBELEKAN (Lantana camara L) SEBAGAI BAHAN PENGAWET ALAMI PADA TIGA JENIS KAYU BUAH-BUAHAN DAN KETAHANANNYA TERHADAP SERANGAN HAMA PERUSAK KAYU - Muhammad Asra Musli; Lusyiani Lusyiani; Diana Ulfah (Universitas Lambung Mangkurat, 2020)
Lesser wood supplies from the forest, which impact on the increasing quality of wood, but timber is still in demand for construction materials. Fruit wood can be used as an effort or alternative to overcome supply shortages or availability of wood. However, most fruit wood has a durable class and low durability. The purpose of this study is to analyze the durability of 3 types of fruit wood, namely, durian wood, rambutan wood and jackfruit wood preserved with preservatives of tembelekan leaf extract, to determine the degree of damage to wood destroying pest attacks. The method used is the length of immersion 3 days, 5 days, and 7 days, with each replication 3 times, with sample tests totaling 27, and 9 test samples as controls, so the total number of test samples is 36. Conclusions obtained from this study is, the degree of damage of wood preserved with the extract of tembelekan leaves has the highest and lowest average value of 37.86% - 26.72%, this condition can be seen that the wood is included in conditions of moderate attack.Keywords: Durian wood; Rambutan; Jackfruit; Tembelekan leaf extract; Degree of damage